HASIL BELAJAR PESERTA DIDIK YANG MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DENGAN TIPE TALKING STICK - Nur Rizqi Arifin; Rizka Andhika Putra; Nina Herlina (Universitas Galuh, 2021)
The low learning outcomes are motivated by various factors including the use of learning models by educators. Research objectives for; 1) The level of student learning outcomes in the initial and final measurements using the Numbered Head Together (NHT) cooperative learning model and the talking stick type cooperative learning model. 2) Differences in student learning outcomes in the final measurement between those using the Numbered Head Together (NHT) cooperative learning model and the talking stick type cooperative learning model. The research method used is the experimental method. The data analysis technique used is homogeneity test, N-Gain, and t-test. The results of the study: 1) There are differences in the level of student learning outcomes in the initial and final measurements using the numbered head together (NHT) cooperative learning model and the talking stick type cooperative learning model. 2) There is an increase in student learning outcomes using the talking stick type of cooperative learning model. With the N-Gain value, students' learning outcomes from pretest to posttest are in the low category. 3) There is an increase in student learning outcomes using the Numbered Head Together (NHT) learning model and those using the Talking Stick Cooperative Learning Model in the posttest measurement in the experimental class and control class.Rendahnya hasil belajar dilatarbelakangi oleh berbagai faktor diantaranya penggunaan model pembelajaran oleh pendidik. Tujuan penelitian untuk; 1) Tingkat hasil belajar peserta didik pada pengukuran awal dan akhir yang menggunakan model pembelajaran kooperatif tipe Numbered Head Together (NHT) dan model pembelajaran kooperatif tipe talking stick. 2) Perbedaan hasil belajar peserta didik pada pengukuran akhir antara yang menggunakan model pembelajaran kooperatif tipe Numbered Head Together (NHT) dengan model pembelajaran kooperatif tipe talking stick. Metode penelitian yang digunakan adalah metode eksperimen. Teknik analisis data yang digunakan adalah uji homogenitas, N-Gain, dan Uji-t. Hasil penelitian: 1) Terdapat perbedaan tingkat hasil belajar peserta didik pada pengukuran awal dan akhir yang menggunakan model pembelajaran kooperatif tipe numbered head together (NHT) dan model pembelajaran kooperatif tipe talking stick. 2) Terdapat peningkatan hasil belajar peserta didik yang menggunakan model pembelajaran kooperatif tipe talking stick. Dengan nilai N-Gain hasil belajar peserta didik dari pretest ke posttest termasuk kategori rendah. 3) Terdapat peningkatan hasil belajar peserta didik yang menggunakan model pembelajaran Numbered Head Together (NHT) dengan yang menggunakan Model Pembelajaran Kooperatif tipe Talking Stick pada pengukuran posttest di kelas eksperimen dan kelas kontrol.